Perlindungan Hukum bagi Pembeli Beritikad Baik dalam Sengketa Kepemilikan Hak atas Tanah yang Beralih Melalui Akta Jual Beli di Hadapan PPAT: Studi Putusan Mahkamah Agung Nomor 5267 K/Pdt/2025 - Michele Diastika Riah Ukur; hasim purba; mahmul Siregar (Jurnal Hukum Lex Generalis, 2026)
Transfer of land rights through a Sale and Purchase Deed executed before a Land Deed Official (PPAT) constitutes an important legal act within the Indonesian land law system, serving as the basis for the transfer and registration of rights. However, in practice, such transfers often lead to disputes, particularly when related to debt guarantees or claims from third parties. This normative legal research employs statutory and case approaches using secondary data analyzed qualitatively. The findings indicate that validity is determined by the fulfillment of the requirements under Article 1320 of the Civil Code, land administration procedures, and the authority of the PPAT. Good faith purchasers are legally protected as long as the transaction is conducted honestly and formally. Supreme Court Decision Number 5267 K/Pdt/2025 affirms that the deed remains valid in the absence of defects of consent and ensures legal certainty for the parties involved.